1997
DOI: 10.1097/00002030-199705000-00004
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-cell-mediated suppression of HIV-1 long terminal repeat-driven gene expression is not modulated by the CC chemokines RANTES, macrophage inflammatory protein (MIP)-1α and MIP-1β

Abstract: RANTES, MIP-1 alpha and MIP-1 beta do not alter HIV-1 LTR-directed gene expression at doses up to 100 ng/ml. Although present in varying concentrations in supernatants derived from CD8+ lymphocytes from HIV-positive individuals, these chemokines are not responsible for the powerful CD8-derived suppressive effect on HIV-1 LTR-mediated gene expression observed in our system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Finally, the persistence of anti-viral activity in CD8 ϩ T or NK-cell supernatant despite the neutralization of known suppressive ␤-chemokines indicates that there are additional soluble mediators of HIV-1-suppressive activity yet to be identified [139,166,[190][191][192], although it is not unreasonable that the newly discovered ligands for CCR5 (e.g., MCP-2) may account for some of this remnant suppressive activity. In any case, it is likely that the identification of these factors will open up yet another branch of inquiry that will help increase our understanding of how the immune system functions in the vise of such a formidable enemy as HIV.…”
Section: Future Directions: Chemokines and Anti-viral Therapymentioning
confidence: 99%
“…Finally, the persistence of anti-viral activity in CD8 ϩ T or NK-cell supernatant despite the neutralization of known suppressive ␤-chemokines indicates that there are additional soluble mediators of HIV-1-suppressive activity yet to be identified [139,166,[190][191][192], although it is not unreasonable that the newly discovered ligands for CCR5 (e.g., MCP-2) may account for some of this remnant suppressive activity. In any case, it is likely that the identification of these factors will open up yet another branch of inquiry that will help increase our understanding of how the immune system functions in the vise of such a formidable enemy as HIV.…”
Section: Future Directions: Chemokines and Anti-viral Therapymentioning
confidence: 99%
“…However, provided that the effects of MIP-1␣, MIP-1␤, and RANTES are eliminated from consideration (e.g., by the use of a test isolate reliant on a receptor other than CCR5 for entry), it can be shown that CAF does not antagonize viral entry (48,88,89). It has also been found that CAF does not inhibit HIV-1 reverse transcription and provirus integration (45,56,89), although supernatants from lymphocytes stimulated with allogeneic cells have been reported to block HIV-1 replication prior to, or at, the integration stage (30).…”
mentioning
confidence: 99%
“…Recent reports have indicated that b-chemokines have no effect on [10] or stimulate [49] HIV-1 replication in macrophages. We have previously reported that the b-chemokines RANTES, MIP1a and MIP-1b do not influence LTR-mediated gene expression, nor do antibodies to these chemokines abrogate the CD8-mediated enhancement of gene expression in monocytic cells [22] or the suppression of gene expression in Jurkat T cells [23]. Additionally, we showed that supernatant of CD8 þ T cells of HIV-1-infected individuals could enhance rather than inhibit HIV replication in human macrophages [28].…”
Section: Human Macrophagesmentioning
confidence: 68%
“…The enhancement of gene expression in monocytic cells treated with CD8 þ T cell culture supernatants correlated strongly with the corresponding level of suppression of gene expression in Jurkat T cells. Further, we have shown that in both monocytic cells [22] and T cells [23] the modulation of LTRmediated gene expression was not induced by the b-chemokines RANTES, macrophage inflammatory protein-1a (MIP-1a) or MIP-1b or by a combination of these chemokines. It was recently reported that the chemokines individually or in combination did not suppress replication of HIV-1 SF33 in CD4 þ T cells [24].…”
Section: Introductionmentioning
confidence: 99%